THE MODELS OF THE MANAGEMENT OPTIMIZATION OF THE ORGANIZATIONAL STRUCTURES OF RUP “BELORUSSIAN METALLURGICAL WORKS” - A. N. Chichko; N. V. Andrianov (Литьë и металлургия, 2006)
The new approach to the mathematic modeling and optimization of interrelation of the control units of the metallurgical enterprise organizational structures is offered. The mathematical model of the organizational structure based on temporary characteristics of control units loading is offered at the example of one of the organizational structures BMZ.